2023
DOI: 10.1002/1878-0261.13505
|View full text |Cite
|
Sign up to set email alerts
|

Soluble galectin‐3 as a microenvironment‐relevant immunoregulator with prognostic and predictive value in lung adenocarcinoma

Susana Torres‐Martínez,
Silvia Calabuig‐Fariñas,
Andrea Moreno‐Manuel
et al.

Abstract: Despite the success of therapies in lung cancer, more studies of new biomarkers for patient selection are urgently needed. The present study aims to analyze the role of galectin‐3 (GAL‐3) in the lung tumor microenvironment (TME) using tumorspheres as a model and explore its potential role as a predictive and prognostic biomarker in non‐small cell lung cancer (NSCLC) patients. For in vitro studies, lung adenocarcinoma (LUAD) and lung squamous carcinoma (LUSC) primary cultures from early‐stage patients and comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…For instance, in a lung adenocarcinoma tumor sphere-model, which mimic an immunosuppressive TME, galectin-3 is released in the TME and modulated the tumor infiltrating immune cells such as regulatory T cells (Treg) ( 34 ). These authors demonstrated that the patients with high soluble galectin-3 levels had more Treg cells, which can inhibit T cells ( 34 ). Treg are also suggested to inhibit γδ T-cell proliferation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a lung adenocarcinoma tumor sphere-model, which mimic an immunosuppressive TME, galectin-3 is released in the TME and modulated the tumor infiltrating immune cells such as regulatory T cells (Treg) ( 34 ). These authors demonstrated that the patients with high soluble galectin-3 levels had more Treg cells, which can inhibit T cells ( 34 ). Treg are also suggested to inhibit γδ T-cell proliferation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%